PENGARUH JARAK TANAM JAGUNG TERHADAP PERTUMBUHAN DAN HASIL JAGUNG SERTA KACANG TANAH YANG DITANAM SEBAGAI TANAMAN SELA - Murdaningsih Murdaningsih; Ambrosius Lai (AGRICA, 2013)
This research aims to find the effect of planting distance on the growth and yield of corn plants which were planted with peanut as intercropping plant, and the impact on the yield of peanuts planted as an intercropping plant as well as to know planting distance for corn and peanut. The experimental design used was randomized Block Design with six treatments namely J1; 55 cm x 40 cm, J2; 60 cm x 40 cm, J3; 65 cm x 40 cm, J4; 70 cm x 40 cm, J5; 75 cm x 40 cm, and J6; 80 cm x 40 cm, while peanuts are planted in the central part of the line, and the corns rows are repeated four times so that there are 24 compartments of research. Results of the study indicated that there is a significant effect on the growth and yield of corn at a distance of 75 cm x 40 cm as well as peanuts planted as an intercropping plant with high corn sidelines range from 32,08 – 132,55 cm, a number of leaves revolve around 4.17 – 9.25 strands, leaf area range from 25,84 – 52.80 cm, corncob diameter of 10.09 cm, corncob weight tan-1 171,33 gram ha-1 5,68 ton, dry weight grain of corn tan-1 80,13 grand ha-1 3,80 ton, as well as the weight of 100 grain of corn is 32,17 gram, whereas number of pods of peanut is 26,63 prolong, pods weight tan-1 88,13 grand ha-1 3,17 ton, dry weight of corn tan-1 31,25 grand ha-1 1,31 ton, and weight of 100 corn grains are 19,22 gram.